TANGGUNG JAWAB APOTEKER TERHADAP KESALAHAN ASISTEN APOTEKER DI LUAR JAM PRAKTEK APOTEKER DI RUMAH SAKIT PERTAMINA DUMAI - Sovia Oktarima; Evi Deliana; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Health development is regulated based on the principles of humanity, balance and benefits based on Government Regulations. The Health Act Number 36 of 2009 concerning Health which states a healthy state, both mentally, socially and mentally, as well as socially that enables a person to obtain a productive and economically social life. The parties participating in health improvement consist of Doctors, Pharmacists, Nurses, and Midwives. Referring to the transfer of pharmaceutical services which are replaced by Indonesian Government Regulation Number 51 of 2009 concerning Pharmaceutical Work, asking Pharmacists for services to educate patients about how to use drugs and allow the use of drugs, assist patients in choosing drugs that can be used without a doctor's prescription, and answer questions patients about the drugs they use. The purpose of this thesis is to first know the pharmacist's responsibility for the errors of the Pharmacist Assistant outside his practice hours, secondly to find out what the patient can do with the mistakes of the Pharmacist Assistant. This type of research is sociological juridical legal research because this study immediately conducted direct observations to the location of research conducted at Pertamina Dumai Hospital, from the results of research that could draw conclusions: first, questions that were questioned by Pharmacists on the delegation of assistance to Pharmacists and Pharmacists as guarantor Pharmacy answer is based on Article 14 of the Government Regulation of the Republic of Indonesia Number 51 of 2009 concerning Pharmaceutical Work, where pharmacists directly bring patients to be hospitalized at the ER then patients get a checkup and treatment until total care, Pharmacists get a warning from the hospital, with SP 1, responsibility requested as a form or action taken by pharmacists managing pharmacies. Second, related to the legal efforts that can be made by patients on the mistakes of pharmacist assistants in this conflict patients try non-litigation pathways, through negotiation channels, negotiations are not only trying to resolve conflicts, but also to repair existing conflicts. Keywords : Responsibility, Remedies, Mistakes, Negotiation